2016
DOI: 10.3348/kjr.2016.17.5.706
|View full text |Cite
|
Sign up to set email alerts
|

Does the Reporting Quality of Diagnostic Test Accuracy Studies, as Defined by STARD 2015, Affect Citation?

Abstract: ObjectiveTo determine the rate with which diagnostic test accuracy studies that are published in a general radiology journal adhere to the Standards for Reporting of Diagnostic Accuracy Studies (STARD) 2015, and to explore the relationship between adherence rate and citation rate while avoiding confounding by journal factors.Materials and MethodsAll eligible diagnostic test accuracy studies that were published in the Korean Journal of Radiology in 2011–2015 were identified. Five reviewers assessed each article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 78 publications
1
18
0
1
Order By: Relevance
“…18 Choi et al identified higher adherence among 63 imaging studies (74%; 20/27 items); their assessment was limited by use of a truncated STARD 2015 checklist. 19 Korevaar et al and Smidt et al also identified that descriptions of test conduct and interpretation were frequently reported. 6,11 Conversely Walther et al found that technical details regarding the index test were reported in less than 50% of the cardiac imaging studies evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…18 Choi et al identified higher adherence among 63 imaging studies (74%; 20/27 items); their assessment was limited by use of a truncated STARD 2015 checklist. 19 Korevaar et al and Smidt et al also identified that descriptions of test conduct and interpretation were frequently reported. 6,11 Conversely Walther et al found that technical details regarding the index test were reported in less than 50% of the cardiac imaging studies evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Walther et al identified higher adherence in their recent evaluation of studies evaluating the accuracy of coronary CT (69%; 14.4/21 items); however, their assessment used a truncated 21‐item checklist and was specific to a single imaging test . Choi et al identified higher adherence among 63 imaging studies (74%; 20/27 items); their assessment was limited by use of a truncated STARD 2015 checklist . Korevaar et al and Smidt et al also identified that descriptions of test conduct and interpretation were frequently reported .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Korean Journal of Radiology recently assessed the quality of its research articles in terms of conformity to the Standards for Reporting of Diagnostic Accuracy Studies (STARD) 2015 guidelines (59) and the adequacy reporting reliability analysis for diagnostic tests (60). The current study revealed another area in which KJR could improve its quality and impact, and we would even suggest some specific measures.…”
Section: Discussionmentioning
confidence: 99%